The Influence of Product Quality and Advertising On Prezt Product Purchase Decisions - Nurma Ros Wungu; Hariandy Hasbi (Dinasti International Journal of Education Management And Social Science, 2024)
In a competitive market environment, it is important for companies to understand the factors that influence consumer behavior in making purchasing decisions. The aim of this research is to investigate the influence of product quality and advertising on consumer purchasing decisions. This study uses a quantitative approach. Data was collected through surveys using questionnaires and literature studies. The data that has been collected is then analyzed using a regression test using the SPSS program. The research results show that product quality and advertising have a positive effect on product purchasing decisions, both partially and simultaneously. Product quality and advertising are two important factors that can influence product purchasing decisions. Consumers who are satisfied with product quality and impressed by product advertising are more likely to buy the product.